CONSIDERATIONS OF NATIONAL CULTURE’S ROLE IN EXPLAINING COMPETITIVENESS - Ivana Načinović Braje; Ivana Šandrk Nukić (Ekonomski Vjesnik, 2017)
This paper aims to map the connection between national culture and competitiveness. Competitiveness includes the set of institutions, policies, and factors that determine the level of productivity of a country. Although competitiveness can be a result of several drivers, we argue that as some of these are people driven, competitiveness must be related to basic underlying assumptions, espoused values and artefacts shared by the people from the observed entity. This makes competitiveness closely related to national and organizational culture. Cross-country analysis has indicated that national culture features do have an impact on national competitiveness. The empirical analysis of global competitiveness index and Hofstede’s cultural variables has shown that uncertainty avoidance index negatively affects competitiveness, but long term orientation index affects competitiveness in a positive way. Therefore, policy makers should be aware that not only tangible economic factors lead to competitiveness but intangible factors such as culture should also be considered in attempts to improve competitiveness.